2008
DOI: 10.1080/15374410802148202
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Family Stress Model on Toddler-Aged Children's Adjustment Among Hurricane Katrina Impacted and Nonimpacted Low-Income Families

Abstract: Hurricane Katrina dramatically altered the level of social and environmental stressors for the residents of the New Orleans area. The Family Stress Model describes a process whereby felt financial strain undermines parents' mental health, the quality of family relationships, and child adjustment. Our study considered the extent to which the Family Stress Model explained toddler-aged adjustment among Hurricane Katrina affected and nonaffected families. Two groups of very low-income mothers and their 2-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 39 publications
4
90
0
1
Order By: Relevance
“…However, when parents did not have a history of MH problems, hurricane exposure influenced positive discipline and parents’ relationship quality for youth; thus, a direct effect on the family environment. This warrants further investigation as Scaramella and colleagues (2008) found that the FSM applied to both disaster-exposed and non-exposed samples.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, when parents did not have a history of MH problems, hurricane exposure influenced positive discipline and parents’ relationship quality for youth; thus, a direct effect on the family environment. This warrants further investigation as Scaramella and colleagues (2008) found that the FSM applied to both disaster-exposed and non-exposed samples.…”
Section: Discussionmentioning
confidence: 78%
“…This has been supported across cultures (Dmitrieva, Chen, Greenberger, & Gil-Rivas, 2004). The FSM has recently been applied to disasters (e.g., Scaramella, Sohr-Preston, Callahan, & Mirabile, 2008), and was related to variation in children’s MH for both disaster exposed and unexposed groups. We examined how parental history of MH problems influenced our family environment indicators, which includes involvement and relationship quality.…”
Section: Conceptual Models Of the Influence Of The Recovery Environmentmentioning
confidence: 99%
“…Given young children's strong dependence upon their parents, recent scholarship suggests that early neighborhood disadvantage is transmitted to children through more immediate experiences such as parenting behavior (Leventhal & Brooks-Gunn, 2000). Reflecting this reality, an emerging literature identifies the interactive and intricate relationships between neighborhood and parenting processes and trajectories of child behavior using an extended family stress model (Church, Jaggers, & Taylor, 2012; Ingoldsby et al, 2006; Kohen et al, 2008; Reising et al, 2013; Scaramella, Sohr-Preston, Callahan, & Mirabile, 2008). This line of research considers non-optimal family process as a pathway through which adverse neighborhood factors affect child development.…”
Section: Parenting As a Mechanism In Neighborhood Influences On Earlymentioning
confidence: 99%
“…More recently, researchers have broadened their focus to examine the effects of disasters on families—for example, by investigating the relationships among parents’ postdisaster psychological distress, parenting practices, and children’s functioning (e.g., Scaramella, Sohr-Preston, Callahan, & Mirabile, 2008; Spell et al, 2008). Little is known, however, about how disasters affect marital and partner relationships in families with dependent children, particularly among families vulnerable to postdisaster adversity.…”
mentioning
confidence: 99%